Detection of HTLV-1 proviral DNA in cell-free DNA: Potential for non-invasive monitoring of Adult T cell leukaemia/lymphoma using liquid biopsy? - Joris, Thomas; Haddow, Jana; Taylor, Graham P.; Cook, Lucy B. M.; Rowan, Aileen G. (Frontiers in Immunology, 2023)
Fragmented genomic DNA is constitutively released from dying cells into interstitial fluid in healthy tissue. In cancer, this so-called ‘cell-free’ DNA (cfDNA) released from dying malignant cells encodes cancer-associated mutations. Thus, minimally invasive sampling of cfDNA in blood plasma can be used to diagnose, characterise and longitudinally monitor solid tumours at remote sites in the body. ~5% of carriers of Human T cell leukaemia virus type 1 (HTLV-1) develop Adult T cell leukaemia/lymphoma (ATL), and a similar percentage develop an inflammatory CNS disease, HTLV-1 associated myelopathy (HAM). In both ATL and HAM, high frequencies of HTLV-1 infected cells are present in the affected tissue: each carrying an integrated DNA copy of the provirus. We hypothesised that turnover of infected cells results in the release of HTLV-1 proviruses in cfDNA, and that analysis of cfDNA from infected cells in HTLV-1 carriers might contain clinically useful information pertaining to inaccessible sites in the body- e.g. for early detection of primary or relapsing localised lymphoma type ATL. To evaluate the feasibility of this approach, we tested for HTLV-1 proviruses in blood plasma cfDNA. CfDNA (from blood plasma) and genomic DNA (gDNA, from PBMC) was isolated from blood from 6 uninfected controls, 24 asymptomatic carriers (AC), 22 patients with HAM patients and 25 patients with ATL. Proviral and human genomic DNA targets were quantified by qPCR using primer pairs optimised for fragmented DNA. We demonstrated that (1) HTLV-1 infection is associated with increased levels of blood plasma cfDNA, (2) proviral DNA is released into blood plasma cfDNA in HTLV-1 carriers and (3) proviral burden in cfDNA correlated with clinical status, raising the possibility of developing assays of cfDNA for clinical use in HTLV-1 carriers.